Talon Metaphor: Grasp and Release Method for Virtual Reality - Yusik Kim; PARK, JUNG MIN (HCI INTERNATIONAL 2018 - POSTERS' EXTENDED ABSTRACTS, PT II, 2018)
In this paper, we present a novel grasp and release method for direct manipulation in virtual reality. We develop a new grasp method in complementary to the proposed release method. Data gloves and smart sensors may achieve high accuracy and speed but users are prone to fatigue after a long use and devices can be expensive. Therefore, we focus our study to develop an algorithm to reduce fatigue and costs of the virtual system. We track the real hands using a depth camera and determine grasp and release states using virtual rays. Without wearing any devices, users are able to grasp and release a virtual object quickly and precisely. Just as eagles use their talons to catch prey, finite virtual rays from the finger tips are used to determine the grasp and release states. We present that our method improves on grasp time, release time and release translational error based on grasp and release tasks. In contrast to the natural interaction metaphor, measured grasp time, release time and the release translational error for our method do not depend on the object types and sizes.
Keywords: Virtual Reality; Virtual Grasp; Bare-hand interaction